Analisis Kemampuan Berpikir Kreatif Matematis Siswa Ditinjau dari Gender - Safitri, Afrianti; Karo-Karo S, Isran Rasyid (Jurnal Pendidikan Matematika : Judika Education, 2024)
This research aims to determine the extent to which there are significant differences in learning outcomes and learning processes with students' mathematical creative thinking abilities when viewed based on gender in students in class XI IPA MAS Muhammadiyah 01 Medan. The method used is a detailed descriptive method with instruments in the form of tests, a semi-structured interview process and supporting documents. Based on the results of the analysis of students' creative thinking abilities in mathematics based on gender, the researchers concluded that the results of students' creative thinking abilities were carried out using tests and interviews. Male students still do not develop the ability to think creatively with very creative interpretations, because there is one indicator of creative thinking ability that is not met, namely flexibility. Meanwhile, female students have developed creative thinking skills with very creative interpretations and meet all the indicators. Overall, male students in class XI Science at MAS Muhammadiyah 01 Medan tend to have lower mathematical creative thinking abilities than female students. Keywords: Creative Thinking, Mathematics, Gender Differences